Eficiencia y facilitación del comercio de las aduanas en la Región Asia Pacífico, 2013-2019 - Paz Castro, Irvin Gilberto (Universidad Michoacana de San Nicolas de Hidalgo, 2025)
This research analyzed customs efficiency in major economies in the Asia-Pacific region between 2013 and 2019, using methodologies such as DEA-Metafrontier analysis, the Malmquist Index, and Tree Regression models. The study evaluated performance among customs offices in major APEC economies, identifying key factors influencing customs efficiency. The results revealed that while customs offices in less-developed economies initially demonstrated greater efficiency (70%), advanced economies managed to surpass them by the end of the period, with Australia, Canada, New Zealand, and Singapore standing out as leaders in best practices. The dynamic analysis confirmed this trend, showing that customs offices in developed countries were the most productive, while economies such as Peru showed notable progress. Among the determinants of efficiency, the Revised Kyoto Convention was the most influential factor (61.39%), followed by the Single Window for International Trade (33.52%) and the Trade Facilitation Agreement (2.68%). In contrast, initiatives such as the SAFE Framework and Authorized Economic Agents did not show a significant impact. Key implications for customs in the Asia-Pacific region. For least developed economies, the results demonstrate that they need to systematically adopt best practices. On the other hand, developed economies, although ranked as benchmarks, must maintain continuous innovation processes, as their leadership is not permanent and depends on sustained improvement. The findings highlight the importance of prioritizing interventions with proven impact (61% attributable to the Kyoto Convention), over measures of limited effectiveness such as the SAFE Framework. Furthermore, they underscore the strategic value of regional cooperation: the changing dynamics of efficiency rankings indicate that peer learning and knowledge transfer are essential. The implications indicate that customs efficiency will depend on implementing evidence-based reforms, maintaining continuous improvement, and strengthening international collaboration in the face of increasingly competitive global trade.

Esta investigación analizó la eficiencia de las aduanas en las principales economías de la región Asia Pacífico entre 2013 y 2019, utilizando metodologías como el análisis DEA-Metafrontera, el Índice de Malmquist y modelos de Regresión Árbol. El estudio evaluó el desempeño entre las aduanas de las principales economías APEC, identificando los factores clave que influyen en la eficiencia aduanera. Los resultados revelaron que, aunque inicialmente las aduanas de economías menos adelantadas mostraron mayor eficiencia (70%), las economías avanzadas lograron superarlas al final del período, destacándose Australia, Canadá, Nueva Zelanda y Singapur como líderes en mejores prácticas. El análisis dinámico confirmó esta tendencia, demostrando que las aduanas de países desarrollados fueron las más productivas, mientras que economías como Perú evidenciaron notables avances. Entre los determinantes de eficiencia, el Convenio de Kyoto Revisado fue el factor más influyente (61.39%), seguido por la Ventanilla Única de Comercio Internacional (33.52%) y el Acuerdo de Facilitación del Comercio (2.68%). En contraste, iniciativas como el Marco SAFE y los Agentes Económicos Autorizados no mostraron un impacto significativo. Las implicaciones clave para las aduanas de la región Asia-Pacífico. Para las economías menos adelantadas, los resultados demuestran que requieren adoptar sistemáticamente mejores prácticas. Por otro lado, las economías desarrolladas, aunque terminaron como referentes, deben mantener procesos de innovación continua, pues su liderazgo no es permanente y depende de la mejora sostenida. Los hallazgos destacan la importancia de priorizar intervenciones con impacto comprobado (61% atribuible al Convenio de Kyoto), frente a medidas de efectividad limitada como el Marco SAFE. Además, subrayan el valor estratégico de la cooperación regional: la dinámica cambiante en los rankings de eficiencia indica que el aprendizaje entre pares y la transferencia de conocimiento son esenciales. Las implicaciones señalan que la eficiencia aduanera dependerá de implementar reformas basadas en evidencia, mantener mejora continua y fortalecer colaboración internacional ante un comercio global cada vez más competitivo.
Instituto de Investigaciones Económicas y Empresariales. Ciencias en Negocios Internacionales
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/19204; info:eu-repo/classification/cti/5; ININEE-D-2025-0686; Aduanas; Comercio internacional; Metafrontera